Mobile Web Application Development in Administration Services in Nursing Department Laboratory - Ivony FN Putriningtyas; Lourdes L Situmorang (Institute of Computer Science (IOCS), 2022)
Many skills laboratories have been depending on various progress technology information for help and make it accessible in management administration in the skill laboratory, including using computers and software/ applications. Study this use type research and development. The development model in the build system uses SDLC (System Development Life Cycle) with the Waterfall model. This study is quasi-experimental research with one group pretest and posttest designs. Applications created containing loan tools and space laboratory, reporting inventory equipment laboratory, documentation activity practicum and system evaluation and reporting. The sample in a study consists of 40 selected respondents using a purposive sampling technique. Test convenience use application uses a questionnaire consisting of 12 questions with a choice very appropriate, appropriate, sufficient appropriate, no suitable, very no appropriate. Data analysis used paired sample t-test. This mobile website is named SiMAPiN based on nine items of need: user, item, category item, unit goods, officers, submissions loan, submission item, category application and borrowing. The analysis shows a change perception of convenience in using application loan tools and goods laboratory (p-value =<0.001). The average change perception is as much as 13.1 points (33.7 – 46.8). The effectiveness of the application of the results is -5.98, which is enormous (>2.0). We conclude that application loan tools and materials, as well as room, can make it easier for stakeholders and laboratories to do management laboratory. Moment conducted testing application, got results that occur enhancement perception to convenience use application. Future research could focus on integration applications this with procurement goods Required laboratory government.